1971
DOI: 10.1159/000208613
|View full text |Cite
|
Sign up to set email alerts
|

Carrier Proteins of Folic Acid Activity in Human Serum

Abstract: The natural folic acid activity (FAA) in the serum, on Sephadex® G-200 gel filtration, is divided into 3 fractions: the first in the band of largemolecular proteins; the second in that of small-molecular proteins; and the third outside the protein band. The second fraction, in the present study, was purified by hydroxyapatite chromatography, with the result that FAA emerged over a narrow area of fractions. In immunoelectrophoresis anddisc electrophoresis this area contained only albumin

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 5 publications
4
26
0
Order By: Relevance
“…Also, Ford and Salter reported some of the properties of unsaturated binder in bovine and human milk (12). Markkanen et al (13) demonstrated that serum folate, as judged by growth of Lactobacillus casei in a microbiological assay, fractionated on Sephadex G-200 into three bands of high molecular weight in addition to the major low-molecularweight fraction that corresponded to "free" folate. When chromatographed on DEAE-Sephadex A-50, the "L. case4…”
Section: Resultsmentioning
confidence: 99%
“…Also, Ford and Salter reported some of the properties of unsaturated binder in bovine and human milk (12). Markkanen et al (13) demonstrated that serum folate, as judged by growth of Lactobacillus casei in a microbiological assay, fractionated on Sephadex G-200 into three bands of high molecular weight in addition to the major low-molecularweight fraction that corresponded to "free" folate. When chromatographed on DEAE-Sephadex A-50, the "L. case4…”
Section: Resultsmentioning
confidence: 99%
“…It has recently been established that a fraction of human serum fol ates is bound to proteins [11] and that part of this fraction is firmly bound to a specific binding protein [15]. This fraction possibly cannot be determined by the radioassay technique but it could be used by L. casei.…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant (40 ml) of the liver suspension was then fractionated immediate ly in column chromatography (Sephadex G-200, Pharmacia, Uppsala), using tech niques described earlier [6]. In each chromatography, 180 samples (10 ml) were collected, and the 3H-activity as well as the microbiological FAA of every sample were measured.…”
Section: Methodsmentioning
confidence: 99%
“…The proteins of both the supernatant of the liver suspension and its chroma tography fractions were determined with the biuret method, and the folic acid with the L. casei method (after the addition of ascorbic acid) as reported earlier [6]. Samples (0.2 ml) of the supernatant of the liver suspension and its chromato graphy fractions were taken into scintillation flasks for the determination of 3H-activity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation